HUBUNGAN KECERDASAN EMOSI DENGAN KEWIRAUSAHAAN PADA MAHASISWA - Ahmad Ifham; Avin Fadilla Helmi (Jurnal Psikologi, 2002)
Bomer Pasaribu (CLDS, 2002), predicted that educated unemployee in Indonesia is 40 million by December 2002. One solution to decrease educated unemployee is being an entrepreneur. Chandra says that a person can be an entrepreneur if he have an optimum emotional intelligence. The research examines there is a positive relationship between emotional intelligence and intrapreneurship at college students. Intrapreneurship at college students is when college students organization use the talents of their creative members to develop innovative products and services for the organizations. Very simple put, intrapreneurhip at college students is entrepreneurship practiced by people within established organizations. The research subject is college students. Data is collected by using scale scale A is Emotional Intelligence Scale according to Patton, Cooper, and Sawaf Theory (2000), consists of (1) emotional literacy, (2) emotional fitness, (3) emotional depth, and (4) emotional alchemy. Scale B is Entrepreneurship Scale according to Peter Ferdinand Drucker (1985), consists of (1) able to see a business chance, (2) have a self confidence and able to behave good to their own and environment, (3) leadership behavior, (4) have inisiative, creativity, and innovation, (5) able to be a hard worker, (6) have a wide vision and good optimism, (7) dare to take a calculated risk, (8) have a sensitivity of critic and comment. The results shows that correlation coefficient level (r) concluded from the two variables is 0,632 with significance level (p) = 0,000 (p < 0,01), so the research hypothesis can be accepted. Emotional Intelligence gives 39,9% effective contribution for Entrepreneurship at college students. Keywords: entrepreneurship, emotional intelligence